In between homeplace + public: a relationship between home, landscape and civic infrastructure in the transformation of everyday life with a focus on sport and recreation in Mamelodi - Masha, Palesa (School of Architecture, Planning and Geomatics, 2024)
Homeplace & the Public aims to showcase the possibilities of infrastructure development and/or redevelopment in the context of township spaces, namely, Mamelodi in Pretoria. A focus being specifically on civic infrastructure like parks, pools, fields, libraries, and halls all to further highlight the duties and responsibilities of the local municipality to the community. Highlighting role players and what goes in the production of space and how power plays itself in the production of said spaces. This, then to elaborate on the perception of the community to understand what makes the community to look after said space. The current state of the civic infrastructure, which I will explore as an extension of the homeplace should offer the same sense of warmth, welcoming and comfort and act as a place of restoration or refuge. Introducing the notion of a safe “homely” spaces outside of the home that can be found in what the government or local municipality offers its people, and not mere walls. A focus will be on public amenities as provided by the municipality. The conditions these infrastructures – dilapidated, underutilised and not well-maintained – call for a transformation to keep up with the interests of the community, and most importantly the youth. A transformation in the regards of how people engage and see said spaces in order to be able to take full advantage of the resources afforded to them and in turn transforming community. The research aims to investigate how the prevalence of good public spaces can aid in the alteration of the social interactions of a community in the ways of social behaviours, institutions, or social relations to one another in turn, transforming cultural and social spaces. The research will have a focus on youth development investigating the interests of the adolescent and young adults in the area. Empirical data research will be undertaken in order to discover the site for what it is and has to offer on the daily. Looking at the role of place-making in projects undertaken or provided by the municipality. Questions on how public space in the form of civic buildings can be designed in a way that is an extension of home to the community, so that the community takes better care of the spaces, at the same time exposing the youth opportunities. With a focus on youth development and empowerment, adequate and proper infrastructure is most prevalent. Looking at what was provided initially with sports fields and schools with ample spaces of play. In seeking ways of relieving oneself, the research will look into current recreational activities that the youth partake in that can be ancillary to sports and recreation as the formidable outlet, the research will aim to unpack the idea of sports bringing people together, both the young and old, to celebrate and take space together at the same time exposing one to various spaces. Youth empowerment and development can lead to social change and transformation. The environment we inhabit has an impact on us.